Pengaruh Kecukupan Modal, Total Asset Trunover, Proporsi Dewan Komisaris Indipenden Terhadap Return On Asset Dengan Corporate Social Responsibility Sebagai Variabel Intervening - Andini Nurwulandari; Dhea Putri Filia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
To make sound financial choices, it is not enough just to look at the company's return on assets; we also need to consider relevant social data. A company's dedication to social responsibility can increase profitability in a number of ways, including increased sales, market credibility, investors in capital markets, and value to owner welfare. Based on this, the aim of this research is to study how CSR affects metrics such as ROA, TAA, and the number of ICs. Nineteen Indonesia Stock Exchange commercial banks were chosen as the sample for this research. SmartPLS 3.28 is utilized to do a descriptive analysis. This study indicated that CSR in Indonesian commercial banks is affected favorably and substantially by three factors: 1) capital sufficiency, 2) asset turnover management, and 3) the proportion of independent commissioners. Commercial banks in Indonesia must maintain a healthy rate of return on assets.